Rationale of cerebral protection devices in left atrial appendage occlusion. Issue 1 (20th October 2016) - Meincke, Felix; Spangenberg, Tobias; Kreidel, Felix; Frerker, Christian; Virmani, Renu; Ladich, Elena; Kuck, Karl‐Heinz; Ghanem, Alexander
Abstract : Aims: Aims of this case‐series were to assess the feasibility of cerebral protection devices in interventional left atrial appendage occlusion (iLAAO) procedures and to yield insight into the pathomorphological correlate of early, procedural cerebral embolization during iLAAO. Methods and Results: Five consecutive patients underwent iLLO flanked by the Sentinel CPS® (Claret Medical, Inc., Santa Rosa, CA) cerebral protection system. Placement and recapture of the Sentinel ® device as well as the iLAAO were successful and safe in all cases. Histomorphometric analysis of the collected filters showed embolized debris in all patients. Acute thrombus was found in three patients, organizing thrombus in four. Interestingly, two patients had endocardial or myocardial tissue in their filters. Conclusions: Cerebral protection during iLAAO with the Sentinel CPS ® device is feasible. Furthermore, this dataset identifies the formation and embolization of thrombus and cardiac tissue as emboligeneic sources and potential future targets to reduce procedural complications. © 2016 Wiley Periodicals, Inc.